2020
DOI: 10.1016/j.ijdrr.2020.101661
|View full text |Cite
|
Sign up to set email alerts
|

Factors motivating Mexico City residents to earthquake mass evacuation drills

Abstract: Evacuation drills may constitute a key activity for preparing for an emergency due to an earthquake. The paper presents the results of an analysis of participants' motivations on the factors leading to conducting drills on 19 September every year in Mexico City; the sample size considered for the analysis was N ¼ 2400. In particular, the following research question has been addressed: What factors predict the likelihood that respondents would report that they agree on conducting mass evacuation drills yearly? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 41 publications
7
18
1
Order By: Relevance
“…Subsequently, disaster preparedness is key during a pandemic, and the majority of this responsibility still falls on individuals, including having a "go kit" ready for emergencies with flashlights, bottled water, face masks, latex gloves, medications, hand sanitizers, soap, disinfectant wipes, and thermometers, etc. This brings our attention to the importance of evacuation drills as a key activity in preparing for an emergency due to a multi-hazard event (e.g., a natural hazard and a pandemic) [95]. Yet, we should not forget about mutual trust between individuals and the government/society [96] which yields to a successful emergency mission.…”
Section: Impact Of Ongoing Pandemic On Natural Hazard-induced Lossmentioning
confidence: 99%
“…Subsequently, disaster preparedness is key during a pandemic, and the majority of this responsibility still falls on individuals, including having a "go kit" ready for emergencies with flashlights, bottled water, face masks, latex gloves, medications, hand sanitizers, soap, disinfectant wipes, and thermometers, etc. This brings our attention to the importance of evacuation drills as a key activity in preparing for an emergency due to a multi-hazard event (e.g., a natural hazard and a pandemic) [95]. Yet, we should not forget about mutual trust between individuals and the government/society [96] which yields to a successful emergency mission.…”
Section: Impact Of Ongoing Pandemic On Natural Hazard-induced Lossmentioning
confidence: 99%
“…As already mentioned, the present study is part of an ongoing research on the residents of the capital city reactions to the usefulness of the SASMEX system in relation to the 2017 earthquakes. The variables considered in the analysis have been those reported in [40]. The non-probability and cross-sectional study were conducted just a few weeks after the two earthquakes; the sample size of the present study is n = 1,644.…”
Section: Ordinal Logistic Regression Modelsmentioning
confidence: 99%
“…The non-probability and cross-sectional study were conducted just a few weeks after the two earthquakes; the sample size of the present study is n = 1,644. (For further details on the data collection and the participants' consent of the study, see [2,40]).…”
Section: Ordinal Logistic Regression Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies reported in the literature investigated human behaviors in earthquakes, hoping to obtain valuable solutions to provide sufficient support for evacuation decision-making [ 4 , 5 ]. Some of the issues being addressed are those related to finding the factors that prompt people to participate in mass evacuation drills [ 6 ]. To conduct quantitative research on the effectiveness of evacuation strategies, one of the most critical tasks is to predict people’s evacuation behavior before the earthquake.…”
Section: Introductionmentioning
confidence: 99%